2002
DOI: 10.1038/sj.ejcn.1601332
|View full text |Cite
|
Sign up to set email alerts
|

Short-term diets enriched in stearic or palmitic acids do not alter plasma lipids, platelet aggregation or platelet activation status

Abstract: Objective: To determine whether healthy males who consumed increased amounts of dietary stearic acid compared with increased dietary palmitic acid through the consumption of commercially available foods, exhibited any changes in plasma lipids, platelet aggregation or platelet activation status. Design: A randomised cross-over dietary intervention. Subjects and interventions: Nine free-living healthy males consumed two experimental diets (stearic acid enriched, diet S, and palmitic acid enriched, diet P) for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 38 publications
1
15
0
2
Order By: Relevance
“…Although dietary intake of SFAs was not correlated with plasma phospholipid SFAs in the MCCS (6), our results suggest that reducing intakes of both palmitic and stearic acids could be beneficial. Short-term feeding studies show that SFA concentrations in platelet phospholipids can be changed by changing intakes of either palmitic or stearic acids (18,19). The KANWU study showed that plasma phospholipid SFA concentrations could be reduced by reducing SFA intake and increasing MUFA intake, with a corresponding improvement in insulin sensitivity (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although dietary intake of SFAs was not correlated with plasma phospholipid SFAs in the MCCS (6), our results suggest that reducing intakes of both palmitic and stearic acids could be beneficial. Short-term feeding studies show that SFA concentrations in platelet phospholipids can be changed by changing intakes of either palmitic or stearic acids (18,19). The KANWU study showed that plasma phospholipid SFA concentrations could be reduced by reducing SFA intake and increasing MUFA intake, with a corresponding improvement in insulin sensitivity (20).…”
Section: Discussionmentioning
confidence: 99%
“…Neither HDL‐C nor plasma TAG differed significantly among the three study diets. Kelly et al (2002) concluded that there is no significant differences between the two diets enriched in C18:0 and C16:0 in plasma lipoprotein concentrations. Based on the food items, the diet enriched in C16:0 was a mixture of fats with triglyceride structures of POP and POo where palmitic acids were esterified at sn ‐1 or sn ‐3 positions which have relatively neutral effects on cholesterol levels.…”
Section: Effects Of Palm Oil and Its Fractions On Blood Lipids And LImentioning
confidence: 99%
“…46 Similarly, stearic acid, a saturated fat commonly found in chocolate, reduces mean platelet volume, an index of platelet activation, in humans. 75,76 …”
Section: Platelet Functionmentioning
confidence: 99%